(untitled) (Research, Society and Development, 2021)
The growth of urban areas over the past decades has interfered with the dynamics of mangrove ecosystems, hampering the provision of ecosystem services. The aim of the present study was to verify the profile of the distribution of plant species, changes in soil structure and parameters that attest to water quality in periurban mangrove ecosystem by the Itanhaém River, in the municipality of Itanhaém (São Paulo, Brazil). The results obtained in this study, carried out between the years 2017 and 2019, were then confronted with studies conducted between the years 1996 and 1998, reflecting a comparison of almost two decades of increase in urbanization, due to the population increase of 31% between 1997 and 2017. The analysis suggested that there was a change in the composition of plant species in the plots studied, especially in those closer to the Itanhaém River. The results of the sediment analysis showed an increase of organic matter in the soil of the collection stations. The analysis of the water quality in the different collection points showed results in disagreement with the parameters established by the Brazilian Resolutions CONAMA 357/05 and 274/00. From the results obtained, it was possible to verify that the speed with which urban expansion and speculation in coastal cities has been taking place and has led to a degradation of the mangrove ecosystem, emphasizing the importance of monitoring coastal vegetation.